(untitled) (European Journal of Economics, Finance and Business Development, 2025)
This scientific article comprehensively analyzes the issue of information management and improving the quality of work processes. Today, the digital transformation processes taking place in society are further increasing the importance of information. Every organization, enterprise and institution in society strives to achieve high efficiency in its activities through the correct collection, analysis, storage and distribution of information. Effective implementation of information management not only improves work processes within the organization, but also serves to ensure social stability, transparency and public control. This strengthens trust between people and ensures the openness of the management system. The article also covers in detail the rational use of information technologies, methods of analyzing digital data and their role in improving the quality of work processes. High-quality organization of any work process increases the efficiency of employees, allows for rational use of resources, and ensures accuracy in the decision-making process. The social significance of these issues is that information management can contribute to the active participation of citizens in state and public governance, the creation of a transparent environment, and overall development. Therefore, improving the quality of information management and work processes is one of the tasks of strategic importance for modern society.